Pengaruh Pergantian Manajemen, Audit Delay, dan Financial Distress Terhadap Auditor Switching pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2015-2019 - Harsi Romli; Reny Aziatul Pebriani; Fenti Melinia Kesuma Putri (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims to investigate the effect of management change, audit delay, and financial distress on auditor switching in banking companies listed on the Indonesia Stock Exchange in 2015-2019. The data used is secondary data obtained through documentation and literature study. The sample in this study amounted to 45 companies. The data were processed using logistic regression analysis. The results prove that management change and financial distress have no positive effect on auditor switching. while audit delay has a positive effect on auditor switching